Age-Related Intestinal Dysbiosis and Enrichment of Gut-specific Bacteria in the Lung Are Associated With Increased Susceptibility to Streptococcus pneumoniae Infection in Mice - McMahan, Rachel H.; Hulsebus, Holly J.; Najarro, Kevin M.; Giesy, Lauren E.; Frank, Daniel N.; Orlicky, David J.; Kovacs, Elizabeth J. (Frontiers in Aging, 2022)
The portion of the global population that is over the age of 65 is growing rapidly and this presents a number of clinical complications, as the aged population is at higher risk for various diseases, including infection. For example, advanced age is a risk factor for heightened morbidity and mortality following infection with Streptococcus pneumoniae. This increased vulnerability is due, at least in part, to age-related dysregulation of the immune response, a phenomenon termed immunosenescence. However, our understanding of the mechanisms influencing the immunosenescent state and its effects on the innate immune response to pneumonia remain incomplete. Recently, a role for the gut microbiome in age-specific alterations in immunity has been described. Here, we utilized a murine model of intranasal Streptococcus pneumoniae infection to investigate the effects of age on both the innate immune response and the intestinal microbial populations after infection. In aged mice, compared to their younger counterparts, infection with Streptococcus pneumoniae led to increased mortality, impaired lung function and inadequate bacterial control. This poor response to infection was associated with increased lung inflammation and an influx of neutrophils into the lungs of aged mice 24 hours after infection. The exacerbated pulmonary immune response was not associated with increased pro-inflammatory cytokines in the lung compared to young mice but instead heightened expression of immune cell recruiting chemokines by lung neutrophils. Bacterial 16S-rRNA gene sequencing of the fecal microbiome of aged and young infected mice revealed expansion of Enterobacteriaceae in the feces of aged, but not young mice, after infection. We also saw elevated levels of gut-derived bacteria in the lung of aged infected mice, including the potentially pathogenic symbiote Escherichia coli. Taken together, these results reveal that, when compared to young mice, Streptococcus pneumoniae infection in age leads to increased lung neutrophilia along with potentially pathogenic alterations in commensal bacteria and highlight potential mechanistic targets contributing to the increased morbidity and mortality observed in infections in age.